1988
DOI: 10.1177/36.10.2458406
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in derivatives of embryonic foregut during prenatal development of the rat.

Abstract: Proteins characteristic for the adult cellular phenotype, i.e., carbamoylphosphate synthetase (CPS) for liver and small intestine, arginase for liver, glutamate dehydrogenase (GLDH) for pancreas, liver, and small intestine, and amylase for pancreas were studied immunohistochemically in rat embryos and fetuses. At distinct developmental stages, subsets of enzymes appear synchronously in the foregut derivatives, suggesting that gene expression in the different organs is regulated by common factors. In contrast t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
20
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
4
20
0
Order By: Relevance
“…In ED 18 rat embryos, the expression of all ornithine cycle mRNAs was homogeneously distributed over the liver lobule. Interhepatocyte differences in the expression of these mRNAs were present, but they were random and not related to the position of the hepatocytes on the portocentral radius of the liver lobule, resembling our previous findings for CPS protein 21 and mRNA. 22 Zonation of mRNA expression first became apparent at ED 20 for OTC, ASS, and ASL (Fig.…”
Section: Aid Hepa 0011supporting
confidence: 89%
See 1 more Smart Citation
“…In ED 18 rat embryos, the expression of all ornithine cycle mRNAs was homogeneously distributed over the liver lobule. Interhepatocyte differences in the expression of these mRNAs were present, but they were random and not related to the position of the hepatocytes on the portocentral radius of the liver lobule, resembling our previous findings for CPS protein 21 and mRNA. 22 Zonation of mRNA expression first became apparent at ED 20 for OTC, ASS, and ASL (Fig.…”
Section: Aid Hepa 0011supporting
confidence: 89%
“…Up to 18 days of development, the expression of ornithine cycle mRNAs in rat liver was low (Fig. 1A-E cellular heterogeneity (compare with Gaasbeek et al 21 and…”
Section: Developmental Expression Of Ornithine Cycle Mrnas Insupporting
confidence: 52%
“…Recent evidence also suggests that intercellular comCorrespondence co R. G. Thurman, Department of Pharmacology, University of North Carolina, Chapel Hill, North Carolina, USA-275 14 partmentation also plays an important role in the regulation of urea synthesis [4, 51. Based on the localization of glutamate dehydrogenase in pericentral regions of the liver lobule, Jungermann and Katz suggested that urea synthesis from ammonia occurs predominantly in pericentral areas [5]. However, carbamoyl-phosphate synthetase I, an important ratedetermining enzyme in urea synthesis, was more active in periportal than in pericentral regions of the liver lobule [6].…”
mentioning
confidence: 99%
“…Although GDH is a ubiquitous enzyme, its concentration varies markedly, with relatively high concentrations in liver, brain, kidney, and pancreas (Herzfeld, 1972). In the liver of rat and human, GDH is expressed exclusively in hepatocytes and can be detected as soon as the liver diverticulum becomes recognizable at 11 days of embryonic development (Gaasbeek-Janzen et al, 1988). GDH activity increases several-fold during prenatal development and reaches its adult level at 2 weeks after birth (Lamers and Mooren, 1981).…”
Section: Introductionmentioning
confidence: 99%